(untitled) (Research, Society and Development, 2020)
According to the National Cancer Institute, 582.590 new cases of cancer were registered in Brazil in 2018, constituting a public health problem. This picture progressively stimulates research and development (R&D) of new antineoplastic agents. However, the R&D process is disrupted and costly when carried out by application methods, so the in silico approach is shown as a viable alternative to these methodologies, making it less expensive and collapsed. In this perspective, the objective of this work was to develop an in silico study aiming to evaluate the pharmacokinetic properties and the potential of tyrosine kinase inhibition of phenolic derivatives of caffeic acid, which are the natural products that are highlighted by their therapeutic potential. According to the results obtained, the compounds used for analysis of the molecular and pharmacokinetic properties of drug candidates. The molecular anchorage study showed that caffeic acid phenol, p-salicildehyde and carvacrol interacted in active site of tyrosine kinase with energy, in kcal.mol-1, of -99.20, -88.07 and -99.90, respectively. By considering, the three phenolic caffeates indicated have potential for tyrosine kinase inhibition and are candidates for antineoplastic agents.